2017
DOI: 10.3892/ol.2017.5882
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR-638 in hepatocellular carcinoma and its clinical significance

Abstract: Abstract. MicroRNAs (miRNAs/miRs) have been identified as important post-transcriptional regulators in healthy liver physiology and liver diseases. However, the clinical significance of miR-638 in hepatocellular carcinoma (HCC) remains unclear. The aim of the present study was to investigate the status of miR-638 expression in HCC and to determine its clinical significance. The expression of miR-638 was evaluated in 60 HCC tissues samples and HCC SMMC-7721, HepG2 and Hep3B cell lines using reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In the present study, miR-454 was observed to be downregulated in GC tissues and cell lines. To clarify the clinical significance of miR-454 in GC, the median value (37,38) was used as the reference value to define the low/high expression of miR-454 expression in tumour tissues. The analysis showed that low miR-454 expression level in GC was correlated with lymph node metastasis, invasive depth and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-454 was observed to be downregulated in GC tissues and cell lines. To clarify the clinical significance of miR-454 in GC, the median value (37,38) was used as the reference value to define the low/high expression of miR-454 expression in tumour tissues. The analysis showed that low miR-454 expression level in GC was correlated with lymph node metastasis, invasive depth and TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of the downregulated miRNAs in chronic patients were found to be associated with carcinogenesis in various organs and tissues, such as miR-1207 [ 40 ], miR-3162-5p [ 41 , 42 ], miR-3196 [ 43 , 44 ], miR-371b-5p [ 45 ], miR-574-5p [ 46 , 47 ], miR-1225-5p [ 48 ], miR-4485 [ 49 ], miR-572 [ 50 ], miR-4299 [ 51 ], miR-3679-5p [ 52 ], miR-3940-5p [ 53 ], miR-638 [ 54 , 55 ], miR-1202 [ 56 ], miR-5787 [ 57 ], miR-1973 [ 58 ], miR-4532 [ 59 ], miR-1275 [ 60 ], miR-4728-5p [ 61 ], and miR-1915-3p [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Previous studies suggest that miR-638 has an important clinical significance in HCC development. 7 , 8 Moreover, knockdown of miR-638 could promote HCC development by increasing cell growth, angiogenesis, migration and invasion. 9 , 10 In addition, miR-638 could be enriched in exosomes, and exosomal miR-638 plays a key role in human cancers.…”
Section: Introductionmentioning
confidence: 99%